Does age influence the success of intra-tympanic steroid treatment in idiopathic sudden deafness?. (October 2015) - Attanasio, Giuseppe; Covelli, Edoardo; Cagnoni, Laura; Masci, Eleonora; Rosati, Davide; Di Porto, Edoardo; Barbara, Maurizio; Monini, Simonetta; Filipo, Roberto
Abstract Conclusions: The present study shows that AGE, DELAY, and PTA_PRE may be considered factors influencing therapeutic success in intra-tympanic steroid therapy. Objective: The aim of the study is to evaluate the relationship between the therapeutic success of intra-tympanic prednisolone therapy and age, in patients affected by idiopathic sudden sensorineural hearing loss (ISSNHL), considering the influence of factors such as delay, gender, and pure tone average (PTA) pre-therapy. Method: This retrospective study involved 402 consecutive patients, affected by unilateral ISSNHL between January 2009 and January 2014. Patients were divided into two groups based on age: group one with 94 patients aged over 65 years and group two with all 402 patients enrolled in the study, including those over 65. Results: PTA recorded before the beginning of the therapy (PTA_PRE) in group one was worse than for group two. In both groups the therapy was significantly effective in improving hearing thresholds, even if PTA_PRE was significant and negatively correlated with success rate. This effect disappeared within the population over 65. On average, each day of DELAY from the onset of hearing loss to the beginning of therapy cuts almost 2% of the possibility to recover. AGE was negative and significant when specified continuously for group two.